KEUSAHAWANAN Menurut Perspektif AL-QURAN - Farahwahida Mohd. Yusof, 1968-, author 181763; Aminudin Hehsan, author; Mohd. Nasir Ripin, author 176517; Zulkiflee Haron, author 176522; Nurul Huda Mansur, author 365872 (Johor Bahru, Johor : Penerbit UTM Press, 2015)
Includes bibliographical references :p.91